The True Cost of AI Pathology Systems: Beyond the Price Tag - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The True Cost of AI Pathology Systems: Beyond the Price Tag The integration of Artificial Intelligence (AI) into pathology—a field critical to disease d...
Keywords: Digital Health; Diagnostics; Patient Care; Artificial Intelligence